2014
DOI: 10.5941/myco.2014.42.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Wood Decay Fungi in South Korea: Polypores from Seoul

Abstract: In Seoul, a majority of plant communities have undergone significant changes over the last few decades; however, how wood decay fungi have responded and adapted to the changes in vegetation remains unknown. Through an ongoing investigation of Korean indigenous fungi, ca. 300 specimens with poroid basidiocarp were collected in Seoul during 2008~2012. Morphological examination and molecular analysis using the internal transcribed spacer and nuclear large subunit ribosomal DNA region sequences helped identify 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…For the identification of polyporoid and corticioid fungi, morphological features are examined and compared to those of known species. The molecular identification method of fungal fruiting bodies with 28S (large subunit; LSU) or internal transcribed spacer (ITS) regions of rDNA sequences has also been used to confirm the morphological identification results in recent works due to the high morphological similarities among closely related species [ 13 15 16 17 18 19 20 21 22 23 24 ]. When nucleotide sequences are generated from the morphologically identified species, the molecular identification method can be used solely when the collected specimens are not suitable for morphological analysis.…”
mentioning
confidence: 99%
“…For the identification of polyporoid and corticioid fungi, morphological features are examined and compared to those of known species. The molecular identification method of fungal fruiting bodies with 28S (large subunit; LSU) or internal transcribed spacer (ITS) regions of rDNA sequences has also been used to confirm the morphological identification results in recent works due to the high morphological similarities among closely related species [ 13 15 16 17 18 19 20 21 22 23 24 ]. When nucleotide sequences are generated from the morphologically identified species, the molecular identification method can be used solely when the collected specimens are not suitable for morphological analysis.…”
mentioning
confidence: 99%
“…Size of pore, basidia, and basidiospore can be used to distinguish A. pubertatis from A. fuscopurpureus . Although smaller basidia size (10.0~13.0 × 3.0~4.5 µm) of A. pubertatis (KUC20080726-14) was proposed [ 8 ], we correct the basidia size as 18.3~20.0 × 6.3~7.9 µm through the re-examination of the originally recorded specimen (KUC20080726-14).…”
Section: Resultsmentioning
confidence: 97%
“…In Korea, all wood rot fungi with purple hymenophores were originally identified as F. rosea [ 14 ]. After detailed morphological and molecular studies, some specimens were identified as A. fuscopurpureus [ 4 ], A. pubertatis [ 8 ], or a new species F. incarnatus [ 24 ]. Although superficially similar, these species can be differentiated based on micromorphology, DNA, and ecology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations